GE_GERICHTE P/11561/2017 vom 10. April 2019 - GE Cour de justice (2019)
LÉSION CORPORELLE SIMPLE ; PLAINTE PÉNALE; RETRAIT(VOIE DE DROIT) ; PRINCIPE DE L'ACCUSATION ; VIOLENCE DOMESTIQUE | CPP.9; CPP.325.al1; CP.217; CP.30; CP.123; CP.179septies; CPP.426.al2; CPP.428.al2; CPP.429.al1.leta; CPP.442.al4